Berm breakwater structures: Final report: Research summary - Juhl, J. (author); Burcharth, H.F. (author); D' Angremond, K. (author); Sigurdarson, S. (author); Holmes, P. (author); Torum, A. (author); Lamberit, A. (author) (DHI, 1997)
A research project on berm breakwater structures was carried out with the overall objective of arriving at a better design basis. Eight European organisations from Denmark, The Netherlands, United Kingdom, Norway, Italy and Iceland participated in the joint research project co-sponsored by the European Commission under the second research and development programme on Marine Science and Technology, MAST II. Studies were made for understanding the physics of berm breakwaters, profile development, problems related to practical engineering applications and three-dimensional (3D) effects. A combination of theoretical work, physical model tests and numerical modelling was used in the project. Features of berm breakwaters are described followed by examples of prototype experience. A summary of the main results of the research project is presented, including forces on individual berm stones, numerical modelling of the flow on and in berm breakwaters and of the berm reshaping, parameter analysis, study of the influence of permeability and stone gradation, results of model tests with scour protection, and analysis of 3D model tests carried out in both deep and shallow water for studying the roundhead and trunk stability. Berm Breakwaters